NOISE EXPOSURE DECREASES THE NUMBER OF SPERMATOZOA IN MALE MICE (Mus musculus L.) EVEN WITH GRAPE SEED EXTRACT (Vitis vinifera L.) ADMINISTRATION - Ghestiara Siregar (Warmadewa University, 2020)
Excessive continuous noises exposure changes the male hormone system which leads to formation of oxidative stress and results in disrupt of semen quality. This condition can be reduced by the use of antioxidants. Grape seed is one of the antioxidants that contains phenol components that have Resveratrol compounds. This research aimed to observe the effect of noise exposure on the number of spermatozoa of male mice given grape seed extract. The method of the research was a post-test only control group design with research subjects of 30 male Mus musculus L. (Swiss Webster) mice divided into 5 groups: group A (treatment control) was not given noise exposure and grape seed extract, group B (negative control) was not given noise exposure and was given grape seed extract, groups C, D, E (treatment group) were given noise exposure with sequential intensities of 65 dB, 85 dB, 105 dB. The treatment was given for 33 days. The results showed that noise exposure with different intensities of 65 dB, 85 dB, 105 dB reduced the spermatozoa count of male Swiss Webster mice even with the administration of grape seed extract. One Way Anova test was used to analyze the data with p-value of 0.001. Conclusion: There were differences in spermatozoa count between the control group and the treatment group. Provision of noise exposure with a value above the threshold limit reduces the number of male Swiss Webster mice spermatozoa given with grape seed extract. Keywords: Number of Spermatozoa, Grape Seed Extract, Noise exposure